Immune Response: A Missed Opportunity Between Vitamin D and Radiotherapy - Yu, Xinyue; Liu, Baocai; Zhang, Ning; Wang, Qian; Cheng, Guanghui (Frontiers in Cell and Developmental Biology, 2021)
Radiotherapy is a curative treatment for several cancer types, mediating various forms of cancer cell death. However, radiation resistance remains a major obstacle in clinical radiotherapy. Increasing evidence indicates that immune response plays a role in reprograming the radiation-induced tumour microenvironment. Intriguingly, radiation-induced immunosuppression possibly overwhelms the immune system’s ability to ablate tumour cells. This induces an immune equilibrium, which we hypothesize is beneficial for sensitizers during cancer radiotherapy. Vitamin D can amplify tumour cell elimination through various forms of cancer cell death when combined with radiation. Similarly, vitamin D can regulate the tumour microenvironment and may even rescue immunostimulation by blocking immunosuppression following radiotherapy. Previous reviews are focused on vitamin D metabolism and epidemic trials, and vitamin D’s synergistic effect with existing therapies remains unknown. This review summarizes vitamin D mediated radiosensitization and radiation immunity, which could contribute to more successful vitamin D-adjuvant radiotherapies.